Wages and International Rent Sharing in Multinational Firms - John W. Budd; Jozef Konings; Matthew J. Slaughter (Institute for the Study of Labor (IZA), 2002)
We use a unique firm-level panel data set of multinational parents and their foreign affiliates to analyze whether profits are shared across borders within multinational firms. Using both fixed-effects and generalized method-of-moments estimators, affiliate wage levels are estimated to respond to both affiliate and parent profitability. The elasticity of affiliate wages to parent profits per worker is approximately 0.03, which can explain over 20 percent of the observed variation in affiliate wages. These results reveal a previously ignored aspect of labor-market rent sharing. They also reveal an important micro-level linkage with potential macro-level implications. International rent sharing can transmit economic conditions across national borders, and can thereby provide an implicit cross-country risk-sharing mechanism.
Keywords: J30; F23; 330; wages; profit sharing; multinational firms; Erfolgsbeteiligung; Lohn; Multinationales Unternehmen; Auslandsniederlassung; Schätzung; Welt